(untitled) (Acta Scientiarum. Health Sciences, 2017)
This study evaluated the association between risk factors and severity of problems related to drug use in secondary school adolescents. This study had the participation of 1192 students from 6th to 9th year of a city in the South of Minas Gerais, Brazil. Data collection occurred through a questionnaire containing: socio-demographic data and the Drug Use Screening Inventory. Drug use was prevalent in adolescents aged 14 and 15 years, atheist, with good family relationships, living with friends/institutions, attended parties once a month, one or two times a week and three and four times a week. There was main damage in the areas of psychiatric disorders, family system and social competence among those who made use of drugs (except alcohol and tobacco). The results point to the need for implementation of preventive strategies of drug use and health promotion in the school context, whereas consumption was associated with significant damage.